Hodgkin's lymphoma, nephrotic syndrome, and echinococcosis cysts: an unusual association and literature review. (2nd January 2019) - Geylis, Michael; Rosen, Guy Beck; Danino, Dana; Schreiber, Ruth; Hassan, Dima; Nalbandyan, Karen; Nahum, Amit
Abstract: We present a 5-year-old female with minimal change nephrotic syndrome (MCNS). Within several months, she became steroid-dependent with progression of edema and ascites. Imaging studies revealed abnormal solid mass and liver cysts and she was diagnosed with both abdominal Hodgkin's lymphoma (cHD) and large hepatic cystic echinococcosis (CE). Association between MCNS and cHL or with CE has been described in the literature in adults and rarely in the pediatric population. We report, for the first time, a simultaneous occurrence of all three: MCNS, cHL, and CE. Literature review and suggested pathophysiologic mechanisms underlying this phenomenon are presented.